The Roles of Muhammadiyah in Shifting Apeman Ritual through State Power and Society - Immanuel, Jimmy Marcos; Lee, Greg; Maizida, Karlina; Pabbajah, Taqiem (IAIN Surakarta, 2018)
This paper aims to discuss the influence of Muhammadiyah in shifting the meaning of Yaa Qowiyyu ritual or Apeman in Jatinom, Klaten. The discussion focuses on examining the role of the dominant group in establishing the mainstream culture in the area. Upon its arrival, Muhammadiyah has established a strong existence in the village and has changed the beliefs of Jatinom residents about the ritual although they still keep the Yaa Qowiyuu existence. Consequently, changes are made in the ritual. The practice is no longer called ‘ritual’ as its term or meaning. Instead, Apeman has turned into a festival. Moreover, the residents’ belief in receiving blessing from the traditional rice flour cake called apem has already gone. Through the ethnographic method, this research shows the ways Muhammadiyah shifted the Jatinom society’s religious perspectives and the critical implications of the efforts to the ritual itself. This paper elaborates the aforementioned problems to observe whether Muhammadiyah did the subtle shifting to the local culture through state power. Using Foucault’s theory about power and knowledge, this research observes the existence of cooperation between Muhammadiyah as the local organization and the state in modifying the ritual and its meaning into the festival. The symbols signifying the cooperation can be seen in this festival. Such cooperation shows that the nationalization and Muhammadiyahization, the process of a society’s shift towards Muhammadiyah, run simultaneously in Jatinom village. Keywords:Ritual, Apeman, and State power